A Critical Review of the End of Development, Post-Developmentalism and Development Paradigm Impasse - Ghodrat Ahmadian (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Development as a specific concept for scientists, politicians, and the public has some validity, so any resistance to it needs great bravery. Despite its validity and importance‚ the development paradigm envisages with many critiques and challenges‚ so the buzzword is impasse in this paradigm. This article proposes some methodological impasses in development paradigm and presents that the post-developmentalism goes beyond these impasses through new perspectives. The key point in this article lies in the fact that in the discussion of post-developmentalism, the role of development has turned from   the state and elites to the society and people. It is worth mentioning that the present review is based on the book entitled “The End of Development? Modernity, Post-Modernity and Development” by Trevor Parfitt who is a Professor at the Department of Political Sciences and International Relations, University of Nottingham, England.